2020
DOI: 10.1155/2020/3642035
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Ketogenic Diet Induces Metabolic Acidosis, Anemia, and Oxidative Stress in Healthy Wistar Rats

Abstract: Background. Ketogenic diet has been used as supportive therapy in a range of conditions including epilepsy, diabetes mellitus, and cancer. Objective. This study aimed to investigate the effects of long-term consumption of ketogenic diet on blood gas, hematological profiles, organ functions, and superoxide dismutase level in a rat model. Materials and Methods. Fifteen male Wistar rats were divided into control (n = 8) and ketogenic (n = 7) groups. Controls received standard diet contained 52.20% of carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Previous studies reporting neuroprotection in animal PD models analyzed effects of shorter periods on the diet—2 weeks prior and 2 weeks after lesion [ 22 ], 11 days prior and 2 weeks after lesion [ 24 ], or 1 week prior and 1 week after lesion [ 23 ]. Recently, Arsyad et al [ 65 ] showed that a 60-day, long-term ketogenic diet consisting of 5.66% of carbohydrate, 86.19% fat, and 8.15% protein induced metabolic acidosis, anemia, and reduced antioxidant enzyme level in healthy Wistar rats. In contrast to our study, they observed significantly reduced glucose levels in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reporting neuroprotection in animal PD models analyzed effects of shorter periods on the diet—2 weeks prior and 2 weeks after lesion [ 22 ], 11 days prior and 2 weeks after lesion [ 24 ], or 1 week prior and 1 week after lesion [ 23 ]. Recently, Arsyad et al [ 65 ] showed that a 60-day, long-term ketogenic diet consisting of 5.66% of carbohydrate, 86.19% fat, and 8.15% protein induced metabolic acidosis, anemia, and reduced antioxidant enzyme level in healthy Wistar rats. In contrast to our study, they observed significantly reduced glucose levels in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Ketonemia induced by a 2-week ketogenic diet in rats resulted in lower circulating insulin and myocardial glycogen store, impaired left ventricular function, and increased myocardial injuries following ischemia–reperfusion in the isolated heart [ 146 ]. Long-term ketogenic diets may potentially exert some systemic effects, such as metabolic acidosis [ 147 , 148 , 149 ], leading to arrhythmogenesis or a mechanoelectrical disturbance. Additionally, ketogenic diets are typically high in saturated fat and cholesterol, which may also induce systemic hyperlipidemia and intracellular lipid accumulation, which leads to increased fatty acid oxidation [ 150 ] and atrial arrhythmogenesis [ 87 , 151 ] due to enhanced ROS production [ 152 , 153 , 154 ].…”
Section: Targeting Cardiac Metabolism As An Upstream Treatment Of Afmentioning
confidence: 99%
“…The ketogenic diet (KD) is a high-fat low-carbohydrate diet that has been used as a nonpharmacologic approach to improve a range of health markers in metabolic disorders [ 158 , 159 , 160 , 161 ], as well as a treatment for intractable epilepsy [ 158 , 162 , 163 , 164 ]. In recent years, studies have suggested that the KD can be therapeutically useful for adjunctive therapy for PD [ 165 ].…”
Section: Nutritive Patterns As a Predictor Of Early Detection Of Park...mentioning
confidence: 99%